Some of the Understudied Dimensions of Ritual - Purzycki, Benjamin Grant (Journal for the Cognitive Science of Religion, 2024)
Ritual: How Seemingly Senseless Acts Make Life Worth Living by Dimitris Xygalatas offers a popularized accounting of an adaptationist view of ritual. By highlighting the author’s own work on the topic, the text itself primarily addresses questions of public rituals’ often extreme costs and its relationship to cooperation. This emphasis, though, comes at the expense of other interesting and/or downstream aspects of ritual that, in my view, deserve more attention. In this commentary, I address a handful of the most relevant to the target text, namely: 1) religious vs. secular rituals; 2) the spatio-temporal distribution of ritual; 3) ritual frequency and timing; 4) the demographic structuring of ritual; 5) ritual’s complicated relationship to control and chance; and 6) ritual as a significant generator of meaningful models about the world.